Balancing Two Conflicting Perspectives on Wiretapping Act: Rights to Privacy and Law Enforcement - Natamiharja, Rudi; Sabatira, Febryani; Banjarani, Desia Rakhma; Davey, Orima Melati; Setiawan, Ikhsan (Al-Risalah, 2022)
The right to privacy is part of fundamental human rights in technological advances. It is outlined under Article 12 of the 1948 Declaration of Human Rights and Article 17 of the International Covenant on Civil and Political Rights. Substantially, the right to privacy prohibits personal data dissemination, including wiretapping, which is considered a violation of human rights. However, applicable laws permit wiretapping when it aims to discover criminal evidence in court. Indonesia authorizes this act under Corruption Eradication Commission Law, Telecommunications Law, Corruption Crime Act, Terrorism Eradication Law, and Psychotropic Law. Unfortunately, these laws have failed to provide a standard mechanism and procedures for conducting the wiretapping act. The substantial insufficiency has made Indonesia a low-ranked country’s privacy rights protection index. This implies the government has failed in balancing the interest of privacy as individual rights and the state's interest in law enforcement. Therefore, this study aimed to examine human rights on privacy, the wiretapping act in law enforcement, and the effort to balance these two rights. It used a normative juridical approach with secondary data. The results showed that Indonesian law has shortcomings that may violate constitutional rights. Therefore, there is a need for a law that comprehensively regulates the mechanisms and detailed procedures for wiretapping.